Psychosocial impact of prognostic genetic testing in the care of uveal melanoma patients: protocol of a controlled prospective clinical observational study. Issue 1 (December 2016) - Erim, Yesim; Scheel, Jennifer; Breidenstein, Anja; Metz, Claudia; Lohmann, Dietmar; Friederich, Hans-Christoph; Tagay, Sefik
Abstract Background Uveal melanoma patients with a poor prognosis can be detected through genetic analysis of the tumor, which has a very high sensitivity. A large number of patients with uveal melanoma decide to receive information about their individual risk and therefore routine prognostic genetic testing is being carried out on a growing number of patients. It is obvious that a positive prediction for recidivism in the future will emotionally burden the respective patients, but research on the psychosocial impact of this innovative method is lacking. The aim of the current study is therefore to investigate the psychosocial impact (psychological distress and quality of life) of prognostic genetic testing in patients with uveal melanoma. Design and methods This study is a non-randomized controlled prospective clinical observational trial. Subjects are patients with uveal melanoma, in whom genetic testing is possible. Patients who consent to genetic testing are allocated to the intervention group and patients who refuse genetic testing form the observational group. Both groups receive cancer therapy and psycho-oncological intervention when needed. The psychosocial impact of prognostic testing is investigated with the following variables: resilience, social support, fear of tumor progression, depression, general distress, cancer-specific and general health-related quality of life, attitude towards genetic testing, estimation of the perceived risk of metastasis, utilization and satisfaction with psycho-oncological crisis intervention, and sociodemographic data. Data are assessed preoperatively (at initial admission in the clinic) and postoperatively (at discharge from hospital after surgery, 6–12 weeks, 6 and 12 months after initial admission). Genetic test results are communicated 6–12 weeks after initial admission to the clinic. Discussion We created optimal conditions for investigation of the psychosocial impact of prognostic genetic testing. This study will provide information on the course of disease and psychosocial outcomes after prognostic genetic testing. We expect that empirical data from our study will give a scientific basis for medico-ethical considerations.